2007
DOI: 10.1007/s10620-006-9462-0
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and the Liver: An Active Interaction

Abstract: Zinc is an essential trace element, exerting important antioxidant, anti-inflammatory, and antiapoptotic effects. It affects growth and development and participates in processes such as aging and cancer induction. The liver is important for the regulation of zinc homeostasis, while zinc is necessary for proper liver function. Decreased zinc levels have been implicated in both acute and chronic liver disease states, and zinc deficiency has been implicated in the pathogenesis of liver diseases. Zinc supplementat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
125
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(134 citation statements)
references
References 189 publications
3
125
1
4
Order By: Relevance
“…Zinc, which was detected to inhibit MMP-2 production seems to be antifibrotic in its action. However, the data concerning protective effect of zinc Page 24 of 57 A c c e p t e d M a n u s c r i p t 24 supplementation are contradictory because in some experiments zinc administration in already cirrhotic animals reduced lipid peroxidation but did not affect liver collagen content [70].…”
Section: Discussionmentioning
confidence: 99%
“…Zinc, which was detected to inhibit MMP-2 production seems to be antifibrotic in its action. However, the data concerning protective effect of zinc Page 24 of 57 A c c e p t e d M a n u s c r i p t 24 supplementation are contradictory because in some experiments zinc administration in already cirrhotic animals reduced lipid peroxidation but did not affect liver collagen content [70].…”
Section: Discussionmentioning
confidence: 99%
“…9 This study found a significant plasma zinc deficiency (43%) in pediatric patients with liver cirrhosis when compared with normal control subjects in the same age group. The results of this study are compatible with those reported by Chin et al, 19 who evaluated the nutritional status of 27 children awaiting liver transplantation and found hypozincemia in 42% of the patients.…”
Section: Discussionmentioning
confidence: 57%
“…A study with adult patients with cirrhosis found an association between zinc deficiency and the increase in the severity of cirrhosis, 9,20 but another study did not. 21 Hambidge et al, 22 A significant correlation between zinc and albumin was found in our study and by other authors who studied patients with liver disease and also cystic fibrosis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Entre as possíveis causas estão: a anorexia e a ingestão reduzida de proteínas animais, o aumento de citocinas ou hormônios que podem afetar o metabolismo do zinco, o aumento de perda renal de zinco e também devido à hipertensão portal, que é responsável pela má absorção dos nutrientes 9 .…”
unclassified